Selenium nanoparticles: Properties, preparation methods, and therapeutic applications. (1st June 2023) - Xiao, Xiang; Deng, Huan; Lin, Xue; Ali, Ahmed Sameir Mohamed; Viscardi, Angelo; Guo, Ziwei; Qiao, Lichun; He, Yujie; Han, Jing
Abstract: Selenium nanoparticles (SeNPs) are a unique type of nano-sized elemental selenium that have recently found wide application in biomedicine. It has been shown that the properties of SeNPs can be varied by different fabrication methods. Moreover, SeNPs have various therapeutic effects in medical applications due to their excellent biological and adaptable physical properties. At the same time, SeNPs can be used as a carrier medium for various therapeutic substances, which can bring out the full curative effects of the drugs. In this review, the differences in bioactivity properties of SeNPs prepared from different substances were reviewed; the therapeutic effects and mechanisms of SeNPs in cancer, inflammation, neurodegenerative diseases, diabetes, reproductive diseases, cardiovascular diseases, and other diseases were discussed; and the importance of the development of SeNPs was further emphasized. Highlights: Biosynthetically produced SeNPs are more stable than physical and chemical SeNPs. SeNPs show superior therapeutic activity in the treatment of various diseases. Due to their high biological activity and low toxicity, SeNPs have great potential.